The Role of Village Fund Policy to minimize the Impact of Covid-19: An Evidence from Indonesia - Anggriawan, Tommy; Haryono, Bambang Santoso; Sentanu , I Gede Eko Putra Sri (Jurnal Ilmiah Administrasi Publik, 2022)
The village fund policy is one of budgeting mechanism promoted by central government of Indonesia for village government to maximize the development in village level. Although some literatures have confirmed the village fund policy contribution for village development, however the current situation of Covid-19 pandemic has generated the demand for village fund policy to minimize the impact of the pandemic. This research is intended to explore the role of village fund policy to minimize the impact of Covid-19 in Indonesia by using desk study toward set of current literatures. The result of this study confirms that there is a shift of principle for allocation of village fund policy from the long of range social and economic impact before the pandemic to the shorter impact during pandemic situation. The new principle has also enable the village government to perform the effective way to minimize the Covid-19 Pandemic impact.